The method of formation of health protection competence of future engineers-technologists of the food industry - Blahyi, O. S. (Problems of Engineer-Pedagogical Education, 2018)
Good nutrition is aimed at strengthening and maintaining the health of consumers, ensuring prevention of diseases, increasing immunity and resistance to external stimuli of the body. Thus, the topical task of the technological engineer of the food industry is the development and introduction of products for sanitary purposes. Therefore, modern vocational education is aimed at the formation of future specialists in the field of health protection competence, namely, systemic knowledge of the special disciplines of the technological direction, as well as knowledge of related disciplines in the medico-physiological and biological fields. However, in the process of training future engineers-technologists in the food industry, there is a contradiction between the need to develop health products and the lack of medico-physiological knowledge about the functioning of the consumer's body. The author developed a method of forming health protection competence of future engineers-technologists of the food industry. Its development is inextricably connected with the goals and content of formation of health protection competence of future specialists. This method of training future specialists involves two successive stages of interaction of the components of the content such as differentiation and integration. The first stage is characterized by the separate formation of medical-physiological, biological, and technological competences. However, it is noted that the formation of the above-mentioned components and the acquisition of health protection competence of future specialists may not be separate. That is, the implementation of health protection competence of future engineers-technologists of the food industry leads to the integration of medical, physiological, biological, and technological competencies in a single unit, which results in the fact that the main components are synthesized into a coherent system. Therefore, the second stage of the teaching method involves the use of consolidation. The implementation of the developed method of forming health protection competence of future engineers-technologists of the food industry fully reflects the objectives and thus the educational content. The developed method of training future professionals focuses on the development and improvement of not only knowledge and skills but also professionally important qualities of future engineers-technologists of the food industry.